(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
Uzbekistan’s banking sector is becoming increasingly digital, and this transformation is reshaping its cybersecurity risk profile. As mobile banking, online payments, and interconnected financial services continue to grow, vulnerabilities are no longer confined to technical infrastructure alone. They increasingly arise from the interaction between human behavior, weak authentication, insecure integrations, fragmented monitoring, and limited incident-response maturity. This article explores the main cybersecurity vulnerabilities affecting Uzbekistan’s banking system and outlines practical directions for improving resilience. The analysis shows that phishing, social engineering, access-control weaknesses, mobile banking and API security gaps, and underdeveloped anti-fraud and governance mechanisms remain among the most serious concerns. The article argues that these risks should be addressed through a layered security model that combines stronger identity protection, secure development practices, integrated monitoring, AI-assisted fraud detection, and sustained awareness-building. In doing so, it provides a more grounded view of how cybersecurity resilience can be strengthened in the national banking sector.